SiRekap : Tantangan dan Potensi Kekeliruan Proses Rekapitulasi Pemilu Serentak di Indonesia - Nurkamiden, Mario (Program Studi Sosiologi, Fakultas Ilmu Sosial Universitas Negeri Gorontalo, 2024)
In realizing the principles of openness and accountability in elections, the utilization of information technology for electronic-based election vote counting is implemented. In the upcoming 2024 elections, the General Election Commission (KPU), as the organizer based on KPU Decision Number 66 of 2024, will employ the Electronic Recapitulation System, abbreviated as SiRekap. SiRekap is an information technology-based application used to publish election vote counting results and the process of election result recapitulation. Furthermore, this application also serves as an aid in the implementation of the vote counting recapitulation process. Therefore, the purpose of this article is to outline the challenges and potential errors in the simultaneous election result recapitulation process using the SiRekap tool in the inaugural simultaneous elections. This article will be described qualitatively descriptively, incorporating social realities regarding SiRekap as a 2024 election policy. The approaches undertaken include statutory, historical, and case approaches. Research results indicate that SiRekap as a 2024 election policy faces challenges and potential errors in its implementation. These potential issues include: firstly, Indonesia's vast territory with diverse geographical regions and minimal supporting infrastructure due to these geographical conditions. Secondly, the uneven understanding of SiRekap among election organizers, not all of whom comprehend it as one of the vote counting methods in the 2024 elections. Meanwhile, potential errors in SiRekap usage in the 2024 election vote counting are: firstly, cyber-attacks and error conditions on the KPU website used, making it vulnerable. Secondly, data input errors in accessing SiRekap by KPPS members are an inseparable part of the potential use of SiRekap in the 2024 elections.